Masyarakat Madani; Pluralitas dalam Isyarat Al-Qur’an - Mia Fitirah Elkarimah (Tarbiyah Departement collaboration with AMCA, 2016)
People who are aware of the rights of citizens and carrying out his duty as a citizen, civilized, uphold humanitarian values, as well as the mastery of science and technology advance in the so-called civil society. This model of society as a dream of idealism and a focus for the world community to this day. Actually this discourse comes alongside the emerging issues of democratization and human rights, which means the same. Madani society is the greatest contribution in building a democracy in a country. And democracy will be realized if the people are aware of respect for human rights. The authors limited the concept of Madani society in the Qur'an cues associated with the concept of baldatun toyyibatun warobbun gofur and the concept of ummah, thus giving rise to one of the characteristics of this community is harmony in plurality.